Analysis of Human Capital and Intellectual Capital Disclosure of The Margin on Net Income - Dian Efriyenty (Enrichment : Journal of Management, 2021)
The survey results on disclosure of financial statements, there were managers who did not disclose their intangible assets. Judging from the development of financial accounting standards No. 19 which states that not many companies have disclosed it. The phenomenon develops along with these standards. The aim of the study is to assess the intellectuals of this standard. The purpose of this study is to analyze the relationship between human capital and financial statement disclosure on net profit margins. The objects of this research are eleven insurance business units. Collect data from reference books and journals and financial reports. Data analysis was used with the help of partial tests and concurrent tests. Based on processed data, capital capital has no impact on margins. Meanwhile, the disclosure of financial statements has an impact on net income. And the results together have an effect on the net profit margin.